The Farmers Perception on Effectiveness of Private Forest Revolving Fund Distribution and Factors Affecting its Repayment: Case in Katibung Subdistrict, South Lampung District, Lampung Province - S Sanudin; San Afri Awang; Ronggo Sadono; Ris Hadi Purwanto (Institut Pertanian Bogor (IPB University), 2016)
Commercial banks are not interested in providing fund for community-based forest plantation development. Therefore, in this case, non bank institutions such Forest Development Funding Center (pusat pembiayaan pembangunan hutan, PPPH) are highly required. This paper is aimed to find out the effectiveness of private forest revolving fund distribution and factors affecting its repayment. The research was conducted during September–December 2014 in 3 Private Forest Farmer Groups in Katibung Sub-District, South Lampung District, Lampung Province. The data was collected through household surveys and in-depth interviews. The household surveys were done using structured questionnaires that included questions related to: characteristics of the borrowers, characteristics of private forest, characteristics of loan, and household perceptions on private forest revolving fund. Household perceptions on private forest revolving fund are pre requirement, loan procedure, loan realization, interest rate, length of repayment periode, and repayment procedure. The effectiveness of private forest revolving fund distribution was analyzed by likert scale and factors affecting repayment of loan was analyzed by logistic regression. The result showed that: 1) private forest revolving fund in three private forest farmer groups in Katibung Sub-District, South Lampung District was effective, 2) income from non-private forest and amount of loan are factors affecting repayment of private forest revolving fund, 3) the faced problem in private forest revolving fund distribution could be overcame by maximizing the role of PPPH field officers in assisting and facilitating private forest revolving fund debitors candidate.